2010
DOI: 10.3109/01612840903342266
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stigma and Other Treatment Concerns and Subsequent Treatment Engagement among Black Mental Health Clients

Abstract: This study examined stigma (both the perception that mental illness is stigmatized and stigma concerns about entering treatment) and other treatment concerns along with subsequent treatment engagement within three months in a sample of 42 black adults referred to public-sector outpatient treatment. Contrary to expectation, perceived stigma of mental illness was unrelated to treatment engagement; however having stigma or other concerns about treatment was associated with increased odds of engagement. Findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Recent reports also support this view (Earnshaw et al, 2012, 2013). These added dimensions permit us to analyze stigma as a multidimensional construct (Alvidrez et al, 2010; Bresnahan and Zhuang, 2011; Sayles et al, 2008) and make our work consistent with the classic conceptualization of stigma as “the co-occurrence” of labeling, stereotyping, separation, status loss, and discrimination (Link and Phelan, 2001). …”
Section: Introductionmentioning
confidence: 65%
“…Recent reports also support this view (Earnshaw et al, 2012, 2013). These added dimensions permit us to analyze stigma as a multidimensional construct (Alvidrez et al, 2010; Bresnahan and Zhuang, 2011; Sayles et al, 2008) and make our work consistent with the classic conceptualization of stigma as “the co-occurrence” of labeling, stereotyping, separation, status loss, and discrimination (Link and Phelan, 2001). …”
Section: Introductionmentioning
confidence: 65%
“…There were few such studies of other forms of stigma or discrimination and their impact on engagement. One study showed that perceived discrimination and devaluation was related to lower engagement with psychotherapy services (8), and another did not (9). A third found a negative relationship between self-stigma and psychosocial treatment adherence (10).…”
Section: Methodsmentioning
confidence: 96%
“…A recent review concluded that CBPR has “great potential for helping reduce mental health treatment disparities among minorities and other underserved populations” (78). Church-based, collaborative research processes could help build trust and reduce stigma associated with research that is especially strong in the African American community (8, 79-81). …”
Section: Discussionmentioning
confidence: 99%